Japan Joins Aukus: Motivations, Progress, And Impact - Tianping Che (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Since its establishment, the AUKUS defense system has encountered significant developmental challenges, primarily due to insufficient internal driving forces, which has created a strategic opportunity for Japan to join AUKUS. Japan seeks to enhance its own defense capabilities, deepen the Japan-U.S. alliance, and define its role in the Indo-Pacific strategy, while also aiming to form close ties with allies in high-tech fields. The U.S. and UK support Japan’s entry into AUKUS and expect to expand the alliance through strategic interaction and technological alliances. However, Australia, considering factors such as geopolitical strategy, institutional construction, and domestic politics, has shown a cautious attitude. Japan’s joining of AUKUS will impact the security structure of the Indo-Pacific region, potentially intensify the regional arms race, and jeopardize the surrounding environment for China’s development.
Keywords: AUKUS Alliance Expansion